Àquelle demande les chercheurs universitaires répondent-ils? - Legault, Marie-Josee (Canadian Journal of Higher Education, 2017)
In this article, author presents the results of an analysis on the practice of collaboration, based on data collected in 1994 by Benoît Godin and Réjean Landry among 1,500 Québec university researchers and on qualitative data collected in 1996. This database allows to shed light on choices researchers make about local organisation of work, a poorly studied matter, and on collaboration between industry or government and university researchers. This allows us to test an hypothesis Gibbons et al recently upholded ( 1 9 9 4 , The new production of knowledge. The dynamics of Science and Research in Contemporary Societies) about the emergence of a new type of organisation of research work. Now, our analysis of the results of this recent inquiry does not allow us to assert that the emergence of any new organisational form, furthering collaboration between academics and non academics, governmental agencies or industrial laboratories, is generalised. Among the special features of this new type, according to Gibbons et al, we note that social or economic usefulness of the research results or relevance for the private sector seem to be important evaluation criteria also. This would suggest an evolution of the kind of demand researchers are eager to fulfil. The researchers' practices vary widely in this regard; they vary among the structures they choose to collaborate in, but they also vary among the behaviors supposed to reveal the emergence of the new type. University researchers in fact fulfil a lot of different sources of demand: universities and students ask for training as much as knowledgeproduction, Québec funding agencies ask for collaboration and knowledge production above all, firms and society ask for helpful knowledge and disciplinary fields call for a coherent development of the corpus of knowledge.